A study on the effect of risk-based auditing on organizational financial performance - Wahyuandari, Wenni; Minarni, Eni; Hariyani, Diyah Santi (Jurnal Konseling dan Pendidikan, 2025)
This study investigates the effect of Risk-Based Auditing (RBA) on organizational financial performance by exploring its integration into auditing practices and its influence on decision-making processes. Using a qualitative research approach, the study employs literature review and library research to synthesize existing findings from academic journals, books, and institutional reports on the subject. Risk-based auditing, a strategic approach to auditing that prioritizes areas of highest risk, has gained prominence in modern auditing practices due to its potential to enhance the accuracy and reliability of financial statements. The review reveals that organizations implementing RBA experience improved financial performance through better risk identification, proactive risk management, and enhanced resource allocation. Furthermore, RBA contributes to better alignment between organizational objectives and financial outcomes, supporting long-term sustainability. However, the study also identifies challenges such as insufficient implementation in some sectors, lack of skilled professionals, and limited awareness of the full benefits of RBA. This paper provides valuable insights into the role of RBA in improving financial outcomes, while highlighting the need for further empirical research to validate its direct impact on organizational performance across different industries. The findings underscore the importance of integrating risk management strategies into auditing frameworks for sustained financial health.